Longitudinal Section of the Tunnel, showing the Shield and the mode of working it. Three Divisions of the Shield of the Thames Tunnel - Fairholt, Frederick William; Wragg (Tufts Archival Research Center, 2008)
This illustration is from Charles Knight's,"London," Vol. 3.